Preharvest melatonin foliar treatments enhance postharvest longevity of cut tuberose via altering physio-biochemical traits - Zulfiqar, Faisal; Moosa, Anam; Darras, Anastasios; Nafees, Muhammad; Ferrante, Antonio; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2023)
Introduction Melatonin (MLT) is a bioactive molecule involved in the physiological functioning of plants. Reports related to preharvest applications of melatonin on the postharvest performance of cut flowers are not available in the literature. Materials & methods This study evaluated the effects of different concentrations of exogenous MLT [0 mM (MT0), 0.5 mM (MT1), 0.7 mM (MT2), 1 mM (MT3)] applied preharvest on the physiological characteristics and postharvest performance of cut tuberose, a globally demanded cut flower. Results & discussion The results revealed that all treatments increased postharvest vase life by up to 4 d. The MT1, MT2, and MT3 treatments increased total soluble proteins (TSP) by 25%, 41%, and 17%, soluble sugars (SS) by 21%, 36%, and 33%, an+d postharvest catalase (CAT) activity by 52%, 66%, and 70%, respectively. Malondialdehyde (MDA) and hydrogen peroxide (H2O2) decreased in all preharvest treatments by up to 23% and 56%, respectively. Proline concentration decreased in all treatments, particularly MT3 (38%). These findings suggest that preharvest MLT treatment is a promising strategy for improving the postharvest quality of cut tuberose.